Campuran Bahan Api Lestarikan Tenaga - Alang Md Rashid, Nahrul Khair (Dewan Bahasa dan Pustaka, 2008)
This article argues about the importance of having a good energy mix in striking balance between various types of energy resources in order to have sustainable energy supply.